Kiai Ahmad Fauzan: Pemikiran dan Peranannya di Kabupaten Jepara 1942-1972 - M. Dalhar; Yety Rochwulaningsih; Dhanang Respati Puguh (Diponegoro University, 2019)
This study focuses on the life, ideas, and role of Kiai Ahmad Fauzan in developing Islamic teachings and national values. Islam and nationalism are two things that interconnected and not contradictory. In Indonesian history, the two of them caused turmoil, even opposition. The purpose of this study is to prove the return of the Moslem spirit which is in line with the development of local religious leaders, primarily through case studies of local scholars in Jepara, such as Kiai Ahmad Fauzan. This study used a historical method, including heuristics, source criticism, interpretation, and historiography. Kiai Ahmad Fauzan was a leader of the Nahdlatul Ulama (NU) who fought through education and politics to uphold the AhlussunahwalJamaah(Aswaja) ideology in Jepara. Fauzan's Islamic and national ideas can be seen from syair[poems] conveyed to the public. Syairbecame a media for propaganda for Kiai Ahmad Fauzan in spreading the religious understanding of Islam Aswaja. It is delivered to the community as reminder and awareness of harmonious religious and national values. His role in the religious and socio-political fields was seen when Japan began occupying Jepara in 1942. He was the target of arrest because of his role as a cleric. Its leadership formed from religious roles carried out mainly through madrasa and da'wah by traveling from one village to another. Kiai Ahmad Fauzan was involved in socio-religious organizations such as the Indonesian Islamic Assembly (MIAI), Indonesian Muslim Council (Masyumi), and NU, especially during the 1955 elections. Kiai Ahmad Fauzan was also trusted by the government to be the first leader of the Ministry of Religion in Jepara after independence revolution.